2018
DOI: 10.1111/bjh.15623
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic recommendations for early stage Hodgkin lymphomas

Abstract: Summary Combined modality treatment has been the standard option for the treatment of early stage Hodgkin lymphoma for several decades. Because of the high success rate and the risk of late toxicities, recent clinical trials have focused on reducing the treatment burden. Field and dose of radiotherapy, and number of cycles of chemotherapy have been successfully reduced, particularly for favourable early stage patients. However, the impact of these treatment reductions on the rate of secondary malignancies rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Classic Hodgkin lymphoma (cHL) is a highly curable cancer. [1][2][3][4] However, due in part to the young age of most patients, treatment-related toxicities and late effects, such as secondary malignant neoplasms (SMNs) and cardiovascular disease (CVD), can adversely affect survival. Cost-per-death analyses have shown that HL has the second highest cost per death or lost-productivity cost (behind only malignant melanoma), 5 and productivity analyses of cancer mortality have shown HL to be the second most costly cancer in terms of lost lifetime earnings.…”
mentioning
confidence: 99%
“…Classic Hodgkin lymphoma (cHL) is a highly curable cancer. [1][2][3][4] However, due in part to the young age of most patients, treatment-related toxicities and late effects, such as secondary malignant neoplasms (SMNs) and cardiovascular disease (CVD), can adversely affect survival. Cost-per-death analyses have shown that HL has the second highest cost per death or lost-productivity cost (behind only malignant melanoma), 5 and productivity analyses of cancer mortality have shown HL to be the second most costly cancer in terms of lost lifetime earnings.…”
mentioning
confidence: 99%